Targeting acute myeloid leukemia stem cells: Current therapies in development and potential strategies with new dimensions. (August 2020) - Tan, Yuxin; Wu, Qiuji; Zhou, Fuling
Graphical abstract: Leukemia stem cells (LSCs) are transformed from normal hematopoietic stem cells (HSCs) or progenitors with the accumulation of mutations and promote the development of acute myeloid leukemia (AML). The resistance of LSCs to common chemotherapy leads to minimal residual disease and relapse. Recent studies have also found that drug-resistant leukemia bulks can regenerate leukemia after chemotherapy. Pre-leukemic HSCs may also be involved in the relapse of AML. According to the current study results, LSCs are still at the center of AML progress and relapse. Drugs targeting LSCs including natural products, synthetic drugs, antibodies or adoptive immune cells have shown beneficial effects in preclinical and clinical researches, especially when combined with existing AML treatments. Due to the complex biological characteristics of LSCs and AML cells, treatment may require dynamic adjustment. The studies of pre-leukemic HSCs and drug-resistant AML cells may provide new dimensions for improving the therapeutic effect in AML. Highlights: Key points of biological characteristics of acute myeloid leukemia stem cells. Different ways that may lead to relapse of acute myeloid leukemia. Recent advances in different strategies for targeting leukemia stem cells. Reduction of relapse via getting close to eradication of leukemia stem cells. Abstract: High relapse rate of acute myeloid leukemia (AML) is still a crucial problem despite considerable advances in anti-cancer therapies. One crucial cause of relapse is the existence of leukemia stem cells (LSCs) with self-renewal ability, which contribute to repeated treatment resistance and recurrence. Treatments targeting LSCs, especially in combination with existing chemotherapy regimens or hematopoietic stem cell transplantation might help achieve a higher complete remission rate and improve overall survival. Many novel agents of different therapeutic strategies that aim to modulate LSCs self-renewal, proliferation, apoptosis, and differentiation are under investigation. In this review, we summarize the latest advances of different therapies in development based on the biological characteristics of LSCs, with particular attention on natural products, synthetic compounds, antibody therapies, and adoptive cell therapies that promote the LSC eradication. We also explore the causes of AML recurrence and proposed potential strategies with new dimensions for targeting LSCs in the future.